Pengembangan Web-Based RT/RW Net Service Information System menggunakan Laravel Framework dengan Digital Payment dan WhatsApp Notification - Salman Miftahur Rizki; Slamet Wiyono; Aang Alim Murtopo (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Information technology development drives the need for a more effective and integrated service management system, particularly for community-based internet services such as RT/RW Net. This research aims to develop a web-based RT/RW Net service information system capable of managing customer data, bill payments, disruption reports, and automatic notifications. The development method employed is the System Development Life Cycle (SDLC) with the Waterfall model, covering the planning, analysis, design, implementation, and testing stages. The system was built using Laravel 13 and SQLite, and is equipped with digital payment, customer management, disruption reporting, WhatsApp notification, and invoice printing features. System testing was conducted using the Black Box Testing method on all main features. The testing results show that all system functions operate according to the specified requirements with a success rate of 100%. The developed system is able to improve the efficiency of customer data management, simplify the payment process, accelerate information delivery to customers, and assist administrators in monitoring services more effectively. This research is expected to become a solution supporting the digitalization of RT/RW Net service management and a reference for developing similar information systems in the future.